2020
DOI: 10.11591/ijphs.v9i1.20402
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical activity on lymphocyte count in smokers who consume black cumin seed (Nigella sativa L.) oil

Abstract: Twenty percent of the total number of human leukocytes is lymphocytes. Lymphocytes are responsible for the control of the adaptive immune system. Physical activity is any body movement that requires energy to do it. Physical activity is related to changes in a person's immunity so that it can reduce the risks of diseases such as obesity, hypertension, diabetes, cancer, and stroke. Black Cumin Seed Oil (BCSO) in various studies has been widely used as a supplement, especially as an immune-modulator. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This research found that BCSO consumption for 20 days increased the adaptive immune response by increasing the number of CD4Th and the expression of IFN-γ and decreasing the number of CD4CD25Treg. The results are in line with previous studies [22]. Thymoquinone increased macrophage phagocytic activity by inducing the enzyme neu4sialidase.…”
Section: Effect Of Bcso Consumption On Antioxidant and Immunity Param...supporting
confidence: 93%
See 1 more Smart Citation
“…This research found that BCSO consumption for 20 days increased the adaptive immune response by increasing the number of CD4Th and the expression of IFN-γ and decreasing the number of CD4CD25Treg. The results are in line with previous studies [22]. Thymoquinone increased macrophage phagocytic activity by inducing the enzyme neu4sialidase.…”
Section: Effect Of Bcso Consumption On Antioxidant and Immunity Param...supporting
confidence: 93%
“…We tested soft capsules containing standardized black cumin seed oil (BCSO) with thymoquinone (2.72%) and fatty acids in the form of caprylate (0.15%), caprat (0.1%), laurat (0.18%), myristate (12.27%), palmitate (0.28%), s tearate (7.99%), o leic (0.07%), l inoleate (2.85%), e icosanoate (3.15%), e ococciate (0.25%), eicosanoenenoate (0.03%), arachidonate (0.03%), eicopentanoat (0.03%), behenat (0.06%), dokoheksanoat (0.04%), teracosanoate (0.02%) and placebo in the form of fish oil capsules [22].…”
Section: Research Instruments and Materialsmentioning
confidence: 99%
“…The National Basic Health Research in 2016 showed that the average consumption of cigarettes per person (aged 15 years or above) was 12 sticks/day [3]. Tobacco smoke has been associated with many degenerative and infectious diseases, i.e., cancer, hypertension and cardiovascular disease, chronic obstructive pulmonary disease (COPD), asthma, diabetes mellitus, and end-stage renal disease (ESRD) [4,5]. The cigarette contains many toxic and immunosuppressant agents, such as dimethylbenzanthracene (DMBA), benzopyrene, carbon ISSN: 2252-8806  Nicotine level associated with decreasing Treg number in smoker healthy volunteers (Akrom) 89 monoxide, and nicotine [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The content of alkaloids can inhibit the proliferation and induction of apoptosis [24]. The tannin content has several pharmacological effects, including antioxidant and anti-free radicals and antimicrobial, anti-cancer, anti-nutritional, and cardioprotective effects [4]. Other research results showed that in vitro water extract and methanol extract of CRR had cytotoxic and antioxidant activity.…”
Section: Figure 2: Relationship Between the Levels Of Crr Methanol Ex...mentioning
confidence: 99%
“…Indonesia is one of the ASEAN countries with the highest number of smokers [3]. Smoking is a risk factor for various degenerative diseases in the community [4]. Along with the high prevalence of smokers, the incidence of cancer in Indonesia has increased.…”
Section: Introductionmentioning
confidence: 99%